Major Histocompatibility Complex Class II (DRB3) Genetic Diversity in Spanish Morucha and Colombian Normande Cattle Compared to Taurine and Zebu Populations - Bohórquez, Michel David; Ordoñez, Diego; Suárez, Carlos Fernando; Vicente, Belén; Vieira, Carmen; López-Abán, Julio; Muro, Antonio; Ordóñez, Iván; Patarroyo, Manuel Alfonso (Frontiers in Genetics, 2020)
Bovine leukocyte antigens (BoLA) have been used as disease markers and immunological traits in cattle due to their primary role in pathogen recognition by the immune system. A higher MHC allele diversity in a population will allow presenting a broader peptide repertoire. However, loss of overall diversity due to domestication process can decrease a population’s peptide repertoire. Within the context of zebu and taurine cattle populations, BoLA-DRB3 genetic diversity in Spanish Morucha and Colombian Normande cattle was analysed and an approach to estimate functional diversity was performed. Sequence-based typing was used for identifying 29, 23, 27 and 28 alleles in Spanish Morucha, Nariño-, Boyacá- and Cundinamarca-Normande cattle, respectively. These breeds had remarkably low heterozygosity levels and the Hardy-Weinberg principle revealed significant heterozygote deficiency. FST and DA genetic distance showed that Colombian Normande populations had greater variability than other phenotypically homogeneous breeds, such as Holstein. It was also found that Spanish Morucha cattle were strongly differentiated from other cattle breeds. Spanish Morucha had greater divergence in the peptide binding region regarding other cattle breeds. However, peptide binding region covariation indicated that the potential peptide repertoire seemed equivalent amongst cattle breeds. Despite the genetic divergence observed, the extent of the potential peptide repertoire in the cattle populations studied appears to be similar and thus their pathogen recognition potential should be equivalent, suggesting that functional diversity might persist in the face of bottlenecks imposed by domestication and breeding.